The Effects of Captan Solution and Bioextract Affecting on Fungal Prevention the Growth of Caladium bicolor Vent.: ผลของสารละลายแคปแทนและน้ำหมักชีวภาพที่มีผลต่อการป้องกันเชื้อราและการเจริญเติบโตของบอนสี (Caladium bicolor Vent.) - Sahawisit, Ratima; Srimongkol, Witjittra; Terdbaramee, Phonthip (Advanced Science Journal, 2024)
The objectives of this research: 1) to compare the captan solution and biofertilizer on the antifungal effect of Caladium bicolor Vent 2) to optimum ratio of biofertilizer for bonbon growth. A 28-day study of captan solution and bio-fermentation solution on prevention of fungal infection of Caladium bicolor Vent. tubers showed that the best formula was the biofermentation of mangosteen peel with neem at a ratio of 75:25%, where the percentage of survival and anti-fungal infection was 75 percent, and causes the highest growth of bonsai. It was found that the highest mean height was 9.42±4.83 cm with the highest average number of leaves 3.00±1.75 leaves.